Solid acid catalyst for synthesizing long-chain alkylbenzene as well as preparation method and application of solid acid catalyst

Through the synergy between MWW molecular sieve and mesoporous modified molecular sieve, combined with oxide binder, a high-efficiency solid acid catalyst for long-chain alkylbenzene synthesis was developed, solving the problems of catalyst deactivation and performance balance, and achieving catalytic effects of high activity, high selectivity and long life.

CN119500253APending Publication Date: 2025-02-25YANKUANG ENERGY R&D CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411677231.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing solid acid catalysts have problems such as catalyst deactivation, poor balance of reaction performance and stability, and complex preparation process in the synthesis of long-chain alkylbenzene.

Method used

Through the synergy between the MWW type molecular sieve and the mesoporous modified molecular sieve, a solid acid catalyst for the synthesis of long-chain alkylbenzene was developed, combined with an oxide binder to form a catalyst system with high activity, high selectivity and excellent stability.

Benefits of technology

This catalyst exhibits excellent performance in the synthesis of long-chain alkyl benzene. It can maintain more than 90% activity after 100 hours of continuous reaction, and the selectivity of monoalkyl benzene can be maintained more than 70%, which is suitable for long-term continuous reactions on industrial scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147332090000081
    Figure BDA0005147332090000081
  • Figure BDA0005147332090000084
    Figure BDA0005147332090000084
  • Figure HDA0005147332100000011
    Figure HDA0005147332100000011
Patent Text Reader

Abstract

The invention discloses a solid acid catalyst for synthesizing long-chain alkylbenzene as well as a preparation method and application of the solid acid catalyst. The solid acid catalyst is a mixed molecular sieve type catalyst. The molecular sieve mainly comprises two molecular sieves, the first molecular sieve is an MWW type molecular sieve, the second molecular sieve is a modified FAU or BEA type molecular sieve, and the molecular sieves are mixed, kneaded and formed by adopting an oxide binder. The solid acid catalyst can be applied to the reaction of long straight-chain olefin or mixed olefin raw materials and benzene to synthesize long-chain alkylbenzene, the reaction condition is mild, the product conversion rate is high, and the monoalkylbenzene selectivity is good. The catalyst also has excellent stability and regeneration performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-value utilization of Fischer-Tropsch synthesis products, and particularly relates to a solid acid catalyst for synthesizing long-chain alkylbenzene, and a preparation method and application thereof. Background Art

[0002] The Fischer-Tropsch synthesis products contain a large amount of olefins, especially linear α-olefins, which are valuable raw materials for the processing and production of high-end chemicals. Long-chain alkylbenzene sulfonates are important surfactants and are widely used in the production of household and industrial detergents. Long-chain alkylbenzene derivatives can be used as lubricant additives to improve the performance of lubricants. Long-chain alkylbenzenes and their derivatives have important applications in oilfield chemicals, such as demulsifiers and viscosity reducers. Other applications include pesticide intermediates, plastic additives, etc. The development of long-chain alkylbenzene synthesis technology can achieve high-value and diversified utilization of high-carbon number fractions in Fischer-Tropsch synthesis products, enrich the product structure of coal indirect liquefaction, and improve the economic benefits of the Fischer-Tropsch synthesis industry. Compared with the traditional petroleum-based alkylbenzene synthesis process, the process route for preparing alkylbenzenes from Fischer-Tropsch products is relatively simple and has more cost advantages.

[0003] Alkylbenzene synthesis is a Friedel-Crafts reaction catalyzed by protonic acid or Lewis acid. The mechanism can be explained by carbon cations or complexes, and the reaction type is an electrophilic substitution reaction of the benzene ring. In the early traditional process, production mainly used traditional acids (such as hydrofluoric acid, aluminum chloride, etc.) as catalysts. However, traditional acid catalysts are highly corrosive and have serious impacts on the environment. There are also problems such as equipment corrosion, difficulty in product separation and purification, and the non-recyclability of catalysts. Therefore, the development of new environmentally friendly, efficient, and recyclable catalysts has become a research hotspot. Solid acid catalytic systems are one of the research and development directions with industrial prospects.

[0004] In recent years, solid acid catalysts have made a series of progress in the field of long-chain alkylbenzene synthesis. Liu Chuangxin et al. (Acta Petrolei Sinica (Petroleum Processing), 2023, 39 (1): 23-34.) used template-enlarged Y-type molecular sieves to effectively improve the life of the molecular sieve. Aslam et al. (Catalysis Today 2014, 227, 187-197.) studied MOR and BEA molecular sieves with different topological structures and Si / Al, and formed a layered porous structure through NaOH desiliconization treatment, which improved the conversion rate of 1-dodecene and the selectivity of the target product alkylbenzene. Patent CN113620766B discloses a method for obtaining lamellar mordenite by double crystallization. Its shortened c-axis diffusion path reduces the blockage of macromolecular pores, thereby slowing down the deactivation of the catalyst.

[0005] In terms of MWW molecular sieves, Yen et al. (Catalysis Science & Technology, 2016, 6 (8): 2715-2724) compared MCM-22 synthesized from different silicon sources, but the optimal lifespan in the alkylbenzene experiment of dodecene was only about 50h. Chen et al. (National Science Review, 2021, 8 (nwaa236)) synthesized a nano-monolayer MWW molecular sieve, and the conversion rate was still around 90% after 120h of reaction, showing good stability. Patent CN116354782A discloses a method for preparing alkylbenzene using a low-stacked molecular sieve catalyst with an MWW topological structure.

[0006] In addition, some other types of solid acid catalysts have been developed. Patent CN101058523A discloses a method for preparing linear alkylbenzene by alkylation reaction under supercritical conditions using a loaded modified molecular sieve catalyst. Patent CN108569945A describes a catalyst composed of an organosilicon zeolite and a binder, which improves catalytic performance by impregnation and fluorine modification. Patent CN115646539A discloses a Y / β composite molecular sieve synthesized by mixing a Y-type prefabricated sol and β and crystallizing it, which has a multi-level pore structure after modification.

[0007] However, although solid acid catalysts show good application prospects in the synthesis of long-chain alkylbenzenes, they still face some challenges. First, the raw materials and products of long-chain alkylbenzenes have large molecular sizes, which are easy to deposit on the catalyst surface or block the pores, resulting in catalyst deactivation. Secondly, the existing solid acid catalytic system still has room for improvement in the balance between catalytic performance and stability. In addition, the preparation process of some high-performance catalysts is complicated, which is not conducive to industrial production. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a solid acid catalyst for synthesizing long-chain alkylbenzene and its preparation method and application. The catalyst not only ensures the selectivity of the reaction, but also improves the diffusion efficiency of macromolecules through the synergistic effect of MWW type molecular sieve and modified molecular sieve containing mesopores. In the synthesis reaction of long-chain alkylbenzene, the catalyst of the present invention shows outstanding performance, has high activity, high selectivity and excellent stability. In particular, after 100 hours of continuous reaction, the catalyst can still maintain more than 90% activity, and the selectivity of monoalkylbenzene can maintain more than 70%. This long-term stable characteristic makes the catalyst of the present invention particularly suitable for long-term continuous reaction on an industrial scale, and has important application value.

[0009] In one aspect, the present invention provides a solid acid catalyst for synthesizing long-chain alkylbenzene, comprising the following components in mass content:

[0010] 10-55% MWW molecular sieve;

[0011] 35-75% modified molecular sieve containing mesopores; and

[0012] 5-20% oxide binder.

[0013] As a preferred solution, the weight percentage of the MWW molecular sieve is 20-40%, the weight percentage of the modified molecular sieve containing mesopores is 50-70%, and the weight percentage of the oxide binder is 8-15%.

[0014] In the above scheme, the MWW molecular sieve has the characteristics of staggered stacking and high mesopore volume, and its mesopore volume is greater than 0.5 cm 3 / g. At the same time, X-ray diffraction analysis was used to characterize the molecular sieve before calcination. It has obvious characteristic peaks on the (002) crystal plane, and the characteristic diffraction peaks of the (101) and (102) crystal planes are overlapped, such as Figure 1 This type of molecular sieve has a unique two-dimensional pore system, including a 10-membered ring sinusoidal pore and a 12-membered ring supercage structure. This structure is conducive to the diffusion of macromolecular reactants and the stability of intermediates. The modified molecular sieve containing mesopores provides a 3-50nm mesoporous structure, which further promotes the mass transfer process of macromolecules. The synergistic effect of the two molecular sieves creates an ideal reaction microenvironment.

[0015] In the above scheme, the modified molecular sieve containing mesopores can be a Y-type molecular sieve or a Beta molecular sieve treated with acid, alkali or steam, and its mesoporous structure helps to improve the diffusion efficiency of reactants and products.

[0016] In the above scheme, the oxide binder can be one or more of alumina, pseudo-boehmite, silica, kaolin or zirconia, which is used to enhance the mechanical strength and stability of the catalyst.

[0017] On the other hand, the present invention further provides a method for preparing the above-mentioned solid acid catalyst, characterized in that it comprises the following steps:

[0018] The MWW type molecular sieve and the modified molecular sieve containing mesopores are prepared respectively;

[0019] Mix the two molecular sieves according to a predetermined ratio;

[0020] Add oxide binder and mix well;

[0021] The solid acid catalyst is obtained by molding, drying and calcining.

[0022] As a preferred embodiment, the hydrothermal synthesis of MWW molecular sieve can be carried out at 120-200°C, and the crystallization time is 72-400 hours. The template used is selected from one of diethyldimethylammonium hydroxide, hexamethyleneimine, and pentamethylammonium bromide. The silicon source is selected from one or more of tetraethyl orthosilicate, silica sol, precipitated silica, and fumed silica. The synthesis method generally includes fully mixing and aging the silicon source, aluminum source, template and deionizer, and selectively adding auxiliary agents. After the mother liquor is obtained, it is continuously loaded into a pressure container, and crystallized in a homogeneous reactor at a certain temperature. After that, the product is separated, washed, dried and calcined, and finally the MWW molecular sieve is obtained.

[0023] As a preferred solution, the modified molecular sieve containing mesopores can be prepared by using commercially available FAU and BEA molecular sieves, wherein the modification treatment includes one or a combination of acid treatment, alkali treatment or steam treatment. The alkali solution used in the alkali treatment is selected from sodium hydroxide solution, a mixed solution of tetrapropylammonium hydroxide and sodium hydroxide, and a recovered liquid after crystallization and solid separation during the preparation of MWW molecular sieves. The concentration of the acid solution and the alkali solution that can be used is 0.1-2 mol / L, the treatment temperature is 40-100°C, and the time is 0.25-24 hours.

[0024] As a preferred solution, the calcination step generally includes two aspects of control: the calcination temperature ranges from 500 to 600°C for 2 to 20 hours; the calcination process is carried out in an air atmosphere or an inert gas atmosphere. The calcination step is crucial for forming a stable catalyst structure.

[0025] In yet another aspect, the present invention further provides the use of the solid acid catalyst in the synthesis of long-chain alkyl aromatics, which include long-chain alkylbenzenes, long-chain alkyltoluenes and long-chain alkylnaphthalenes.

[0026] The catalyst of the present invention has excellent reaction performance characteristics in the synthesis reaction of long-chain alkylbenzene. The typical reaction conditions are: temperature 100-180°C, pressure 0.5-4.0MPa, mass space velocity (WHSV) 0.1-10h -1 , the molar ratio of benzene to olefin is 6:1-30:1. The olefin may be C 10 -C 20 normal olefins within the range, or C 10 -C 20 A mixture of normal olefins and isoolefins within the range of C 10 -C 20 The range contains a mixture of normal and iso-alkanes and aromatics, which provides flexibility in the synthesis of alkylbenzenes with different carbon chain lengths.

[0027] The catalyst of the present invention has the characteristic of being able to be regenerated repeatedly. The regeneration method thereof comprises: 1) using benzene or a mixture of benzene and other light hydrocarbons in a certain proportion as a flushing agent, and washing and regenerating the catalyst at a certain temperature and pressure. The hydrocarbons mentioned herein include light chain alkanes or cycloalkanes with a carbon number of less than 10. The flushing temperature range is selected from 150-280°C, and the flushing pressure range is selected from 1.5-4.0MPa. 2) calcining and regenerating the catalyst in an atmosphere containing a certain proportion of oxygen, wherein the calcining process is heating from a relatively low starting temperature to a certain temperature platform at a certain heating rate, and calcining at this temperature for a certain time, and then continuing to heat to a higher temperature platform for calcining for a certain time, and regeneration is completed after calcining at 1 to 4 temperature platforms. The oxygen ratio mentioned herein is 0-30%, and the rest is inert gas. The heating rate mentioned herein is 0.5-3.0°C / min, the calcining temperature is selected from the range of 150-650°C, and the calcining time is selected from 1-20 hours.

[0028] Under these optimized reaction conditions, by comparing the reaction results of the specific embodiments and comparative examples, the catalyst exhibits significant performance advantages.

[0029] (1) High activity: The conversion rate of normal olefins can be maintained above 90% for reaction time of 100 hours or more, ensuring efficient utilization of raw materials.

[0030] (2) High selectivity: After a reaction time of 100 hours or more, the selectivity of monoalkylbenzene can be maintained at more than 70%, which greatly reduces the generation of by-products and simplifies the subsequent separation and purification process.

[0031] (3) Excellent stability: Under the same level of reaction time, the catalyst activity of the present invention is stable, which significantly extends the service life and can reduce production costs.

[0032] (4) Good mesoporous structure: The mesoporous structure of the synthesized MWW type molecular sieves and modified molecular sieves is conducive to the diffusion of reactants and products, further improving the catalytic efficiency.

[0033] The catalyst system of the present invention has many advantages in design and application:

[0034] (1) Catalyst composition optimization: MWW molecular sieves and modified molecular sieves can balance the acidity to achieve the desired optimal catalytic activity, while providing a hierarchical pore structure that optimizes selectivity. The binder further improves the overall stability of the catalyst. Its synergistic effect not only ensures the selectivity of the reaction, but also improves the diffusion efficiency of macromolecules, thereby significantly extending the catalyst life while maintaining high activity. This unique combination gives full play to the advantages of each component. The mesoporous and hierarchical pore structure facilitates product diffusion and reduces the contact time of carbon precursors inside the molecular sieve, thereby reducing the blockage of the pores by heavy materials, ultimately improving the catalyst stability.

[0035] (2) The preparation method is easy to scale up: conventional molecular sieve synthesis and modification methods are used, which is conducive to industrial application.

[0036] (3) Mild reaction conditions: Relatively low reaction temperature and pressure not only reduce energy consumption, but also reduce the requirements for reaction equipment and improve safety.

[0037] (4) Environmentally friendly: As a solid acid catalyst, it is easy to separate and recycle from the reaction system, reducing the generation of waste and conforming to the concept of green chemistry. As a green catalytic technology, it can effectively replace traditional liquid acid catalysts and reduce environmental pollution and equipment corrosion.

[0038] (5) High product quality: High selectivity ensures product purity, reduces the cost of subsequent separation and purification, and improves overall production efficiency.

[0039] Compared with the prior art, the catalyst of the present invention can increase the conversion rate of alpha-olefin by 10-25% and the selectivity of monoalkylbenzene by 10-50% in the alkylation reaction of long-chain alpha-olefin and benzene, and at the same time, the service life of the catalyst is extended by 50-100%.

[0040] The catalyst system provided by the present invention has significant advantages in the synthesis of long-chain alkylbenzenes, not only improving reaction efficiency and product quality, but also having good economy and environmental friendliness. Its unique composition and optimized preparation method make it have broad application prospects in multiple fields. The catalyst of the present invention is not only suitable for the synthesis of long-chain alkylbenzenes, but also can be applied to the alkylation reaction of other aromatic hydrocarbons. For example, it can be used to produce compounds such as long-chain alkyltoluene and long-chain alkylnaphthalene, which are widely used in the fields of lubricating oil additives, surfactants, etc. In addition, the catalyst is of great significance in the high-value utilization of Fischer-Tropsch synthesis products, and can improve the economic benefits of coal-to-oil technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The X-ray diffraction spectra of catalyst samples A1 and B1 obtained in Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be noted that after reading the content covered by the present invention, for those of ordinary skill in the art, some changes and improvements can also be made without departing from the inventive concept, and these all belong to the protection scope of the present invention. The various commonly used reagents used in the embodiments are all commercially available products.

[0043] The conversion rate and selectivity specifically refer to the conversion rate of normal olefins in the alkylbenzening agent and the selectivity of monoalkylbenzene in the product, respectively, and the calculation formulas are as follows.

[0044] Normal olefins (C = ) conversion rate:

[0045]

[0046] in and It is the amount of normal olefin substance before and after the reaction.

[0047] Monoalkylbenzene (AB) selectivity:

[0048]

[0049] Where N AB is the amount of monoalkylbenzene in the product, N t.p. It is the amount of substance of all products (excluding excess unreacted benzene). represents the mass fraction of normal olefins consumed in the reaction to convert into monoalkylbenzene, and is the mass fraction of normal olefins before and after the reaction. Indicates the mass fraction of linear and branched alkylbenzenes in the product. MW AB and MW C = represent the mass-weighted average molecular weights of monoalkylbenzene and normal olefins, respectively.

[0050] Example 1

[0051] Take 1513g of diethyldimethylammonium hydroxide (20% aq), add 65g of aluminum sec-butoxide (96%) under vigorous mechanical stirring. Continue stirring and slowly add 1609g of tetraethyl orthosilicate and 808g of water. Continue stirring at high speed for about 1.5 hours until it is homogeneous. Then the reaction mother liquor is removed from alcohols by rotary evaporation and concentrated. Then take about 700g of the reaction mother liquor, add about 388g of diethyldimethylammonium hydroxide, and 8g of sodium chloride dissolved in an appropriate amount of deionized water, and continue stirring for about 40 minutes until it is homogeneous. Finally, take an appropriate amount of the mother liquor, put it into the PTFE liner and the reactor, seal it tightly, and dynamically crystallize it at 150°C in a homogeneous reactor for 7 days. After completion, wash with deionized water, separate and dry to obtain catalyst component A1. After analysis, the BET specific surface area is 459m 2 / g, and the mesopore volume is 0.81cm 3 / g.

[0052] Industrial-grade HY molecular sieve (Si / Al=2.6) was used as the raw material, treated at 150°C for 4 hours in a steam atmosphere, and then treated with 1.5M nitric acid solution at 80°C for 1 hour. After completion, it was washed to neutrality and dried to finally obtain high-silicon mesoporous Y molecular sieve (Si / Al≈18), i.e., catalyst component A2. After analysis, the BET specific surface area was 613m 2 / g, and the mesopore volume is 0.21cm 3 / g.

[0053] Take 25.0g of catalyst component A1 powder and 71.7g of catalyst component A2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. Use 34.8g of pseudo-boehmite (75% dry basis) as the adhesive, and activate it into a gel with 110.9g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, dry them at 60°C for 65 hours, then calcine them at 540°C in a flowing nitrogen atmosphere for 4 hours, then switch to static air and continue calcining for 6 hours, and finally obtain catalyst A.

[0054] Comparative Example 1

[0055] First, 8.2 g of sodium aluminate (53% Al2O3, 41% Na2O) and 4.2 g of NaOH were dissolved in 1157 g of water. Then, 68 g of hexamethyleneimine (98%) was added to the solution and stirred at 50°C for more than 20 minutes. 81 g of fumed SiO2 (specific surface area of ​​200 m2) weighed in advance was slowly added in batches. 2 / g), and continue stirring for about 30 minutes or more until it becomes homogeneous. A certain amount of the mother liquor is transferred to a PTFE liner and placed in a reactor for tight reinforcement. Crystallization is carried out in a homogeneous reactor at 150°C for 7 days, followed by repeated water washing (pH <10) and centrifugation. The collected solid is continued to be dried at 60°C for 24 hours, and then calcined at 580°C for 3 hours to finally obtain catalyst component B1. After analysis, the BET specific surface area is 446m 2 / g, mesopore volume is 0.25cm 3 / g.

[0056] Take 45.0g of catalyst component B1 powder and 59.3g of catalyst component A2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. Use 29.6g of pseudo-boehmite (75% dry basis) as the binder, and activate it into a gel with 94.4g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, dry them at 60°C for 24 hours, and then calcine them at 580°C for 3 hours in a static air atmosphere to finally obtain catalyst B.

[0057] Comparative Example 2

[0058] Take 104.4g of catalyst component A2 powder, add a certain amount of deionized water and stir evenly. Use 34.8g of pseudo-boehmite (75% dry basis) as the binder, and activate it into a gel with 110.9g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, dry them at 60°C for 36 hours, and then calcine them at 540°C for 3 hours in a static air atmosphere to finally obtain catalyst C.

[0059] Example 2

[0060] 91 g of aluminum sec-butoxide was added to 2015 g of diethyldimethylammonium hydroxide (20% aq), and then 1012 g of silica sol (specific surface area> 100 m 2 / g) and 9g of water. 1569g of the mother liquor was transferred to a PTFE liner, then loaded into a reactor and sealed. After aging at 100°C for 3 days, 22.5g of tetramethylammonium chloride and 116g of water were added to the mother liquor, and after sufficient stirring for homogenization, an appropriate amount of the mother liquor was loaded into a homogeneous reactor and dynamically crystallized at 150°C for 7 days. After crystallization, it was repeatedly washed with water until neutral and centrifuged, and then dried at 80°C overnight to obtain catalyst component D1. After analysis, the BET specific surface area is 408m 2 / g, and the mesopore volume is 1.06cm 3 / g.

[0061] Industrial grade HY molecular sieve (Si / Al=2.6) was used as raw material and NH4 +After the exchange, the mixture was treated in a steam atmosphere at 600°C for 4 hours. Then, NH4 + Exchange, then exchange with 0.1MLa(NO3)3 solution at 90℃ for 1 hour. Continue to treat at 650℃ in a water vapor atmosphere for 4 hours, and then use low concentration hydrochloric acid to pickle once. Use the recovered liquid after crystallization in the preparation of catalyst component D1, and further treat at 65℃ for 1 hour, then separate and dry at 60℃ overnight. Then repeat NH4 + Ion exchange, drying and calcination were performed to finally obtain catalyst component D2. After analysis, the BET specific surface area was 621 m 2 / g, and the mesopore volume is 0.18cm 3 / g.

[0062] Take 60.0g of catalyst component D1 powder and 94.3g of catalyst component D2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. The adhesive uses 22.9g of pseudo-boehmite (75% dry basis), and is activated into a gel with 72.9g of nitric acid solution (4%, aq.). The above components are mixed and bonded into shape, dried at 80°C for 70 hours, and then calcined for 3 hours at 540°C in a flowing nitrogen atmosphere, and then switched to static air and continued calcination for 16 hours to finally obtain catalyst D.

[0063] Example 3

[0064] Add 82g of aluminum sec-butoxide to 1332g of diethyldimethylammonium hydroxide (20% aq) and stir vigorously to mix. Slowly add 408g of precipitated SiO2 (white carbon black) under continuous stirring. In addition, dissolve 12g of potassium chloride and 36g of tetramethylammonium chloride in 106g of deionized water. Then transfer the salt solution to the silicon-aluminum mother liquor. After homogenizing for 15 minutes under high-speed stirring, take an appropriate amount of the mother liquor into a PTFE liner, load it into a reactor, seal it tightly, load it into a homogeneous reactor, and dynamically crystallize it at 150°C for 12 days. After that, wash it repeatedly with water until it is neutral and centrifuge it. After sufficient drying, the catalyst component E1 is obtained. After analysis, the BET specific surface area is 412m 2 / g, and the mesopore volume is 1.01cm 3 / g.

[0065] Catalyst component A2 was used as the raw material, and a mixed alkali solution (0.1 MOH - , TPA + / OH - =0.75), and then the pore expansion treatment was carried out at 65°C for 0.5h. Then it was separated by water washing and dried at 60°C overnight. Then the NH4 +Ion exchange, drying and calcination were performed to obtain catalyst component E2. The BET specific surface area was 617 m 2 / g, and the mesopore volume is 0.22cm 3 / g.

[0066] Take 30.0g of catalyst component E1 powder and 81.5g of catalyst component E2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. The adhesive uses 29.6g of pseudo-boehmite (75% dry basis), and is activated into a gel with 94.4g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, first dry them at 60°C for 48 hours, then heat them to 90°C and continue drying for 24 hours. After completion, calcine them at 540°C in a flowing nitrogen atmosphere for 4 hours, then switch to static air and continue calcining for 16 hours to finally obtain catalyst E.

[0067] Example 4

[0068] First, 376g silica sol (specific surface area> 200m 2 / g) add 115g of deionized water, take 14.5g of sodium aluminate and 6.5g of sodium hydroxide and dissolve them in 350g of deionized water. The above two components are fully mixed, and then 65g of hexamethyleneimine (98%) and 115g of deionized water are added. Continue to stir at high speed for homogenization, and add 2g of catalyst component B1. Then dynamically crystallize at 170°C for 5 days. After completion, repeatedly wash with water and centrifuge, and then dry at 60°C overnight. Continue to take 50g of the obtained solid, add 135g of deionized water, and then add 750g of hexadecyltrimethylammonium bromide solution (25%) and tetrapropylammonium hydroxide (40%). After reflux treatment at 80°C for 24 hours, filter out the solid. Take 25g of the solid and add 125g of tetraethyl orthosilicate, and reflux treatment at 80°C and nitrogen atmosphere for 24 hours. The separated solid was added with 2M ammonium nitrate solution and treated for 6 hours at 80°C under nitrogen atmosphere, and the treatment was repeated once. + Ion exchange was performed to finally obtain catalyst component F1. After analysis, the BET specific surface area was 592 m 2 / g, and the mesopore volume is 0.52cm 3 / g.

[0069] Industrial grade Hβ molecular sieve was used as raw material, 0.1M NH4Cl solution was used for ion exchange, followed by centrifugation and water washing, drying at 60°C and calcination at 650°C for 3h, repeated three times. Catalyst component F2 was obtained. After analysis, the BET specific surface area was 678m 2 / g, mesopore volume is 0.20cm 3 / g.

[0070] Take 73.8g of catalyst component F1 powder and 73.8g of catalyst component F2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. Use 32.8g of kaolin as a binder, and use 69.7g of nitric acid solution (4%, aq.) to activate it into a gel. Mix the above components, bond them into a shape, dry them at 60°C overnight, and then calcine them in a static air atmosphere for 6 hours to finally obtain catalyst F.

[0071] Example 5

[0072] Take 153.7g of diethyldimethylammonium hydroxide and add 4.5g of aluminum sec-butoxide under vigorous mechanical stirring. Under continuous stirring, slowly add 182.5g of tetraethyl orthosilicate and 140.4g of deionized water. Continue stirring for 2 hours until homogeneous. Then concentrate by rotary evaporation to obtain mother liquor g1. Then prepare mother liquor g2: add 10.1g of aluminum sec-butoxide to 44.8g of diethyldimethylammonium hydroxide that is also vigorously stirred. Continue to stir and continue to add 16.0g of tetraethyl orthosilicate and 9.5g of deionized water. Continue stirring for 4.5 hours until transparent and homogeneous. Take 63.7g of mother liquor g1 and 12.5g of mother liquor g2 and mix them evenly, and continue to add 23.8g of diethyldimethylammonium hydroxide under continuous stirring. After stirring for 30 minutes until homogeneous, take an appropriate amount of the mother liquor to the PTFE liner, load it into the reactor and seal it tightly. Installed in a homogeneous reactor, dynamic crystallization at 150°C for 14 days. After the crystallization reaction is completed, deionized water washing and centrifugation are repeated. Then dried at 60°C overnight, calcined at 540°C for 16 hours in a static air atmosphere, and finally catalyst component G1 was obtained. After analysis, the BET specific surface area is 447m 2 / g, and the mesopore volume is 1.19 cm 3 / g.

[0073] Use industrial grade USY molecular sieve (Si / Al≈4) as raw material, wash with low concentration hydrochloric acid, repeat once. After completion, wash to neutral and dry. Use a mixed alkali solution (0.2MOH - , TPA + / OH - =0.5), and then the pore expansion treatment was carried out at 60°C for 0.5h. Then it was separated by water washing and dried at 60°C overnight. Then the NH4 + Ion exchange, drying and calcination were performed to obtain catalyst component G2. The BET specific surface area was 754 m 2 / g, mesopore volume is 0.20cm 3 / g.

[0074] Take 52.2g of catalyst component G1 powder and 52.2g of catalyst component G2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. Use 34.8g of pseudo-boehmite (75% dry basis) as the adhesive, and activate it into a gel with 110.9g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, first dry them at 60°C for 24 hours, and then calcine them at 540°C for 20 hours in a static air atmosphere to finally obtain catalyst G.

[0075] Example 6

[0076] Under stirring, add 16g of aluminum sulfate solution (47%) to 15g of NaOH solution (25%) and 44g of deionized water. After stirring evenly, continue to add 100g of pentamethylammonium bromide (20%, aq.). Continue stirring for 2 hours until homogeneous, then continue to slowly add 25g of precipitated SiO2 (white carbon black), and homogenize under high-speed stirring. Then transfer a certain amount of the mother liquor to the PTFE liner, load it into the reactor and seal it tightly. Install it in a homogeneous reactor and statically crystallize it at 170°C for 80 hours. After the crystallization is completed, wash and filter it repeatedly with water, and dry it at 120°C overnight to obtain the catalyst component H1. After analysis, the BET specific surface area is 548m 2 / g, and the mesopore volume is 0.93cm 3 / g.

[0077] Catalyst component A2 was used as the raw material, and a mixed alkali solution (0.1 MOH - , TPA + / OH - =0.5), and then the pore expansion treatment was carried out at 65°C for 0.5h. Then it was separated by water washing and dried at 60°C overnight. Then the NH4 + Ion exchange, drying and calcination were performed to obtain the catalyst component H2. The BET specific surface area was 635 m 2 / g, and the mesopore volume is 0.24cm 3 / g.

[0078] Take 99.0g of catalyst component H1 powder and 89.1g of catalyst component H2 powder, mix them thoroughly, add a certain amount of deionized water and stir evenly. Use 19.8g of kaolin as the adhesive, and activate it into a gel with 42.1g of nitric acid solution (4%, aq.). Mix the above components, bond them into shape, first dry them at 60℃ overnight, then heat them to 120℃ and dry them for 16 hours, and then calcine them at 540℃ in a flowing nitrogen atmosphere for 2 hours, then switch to static air and continue calcining for 12 hours, and finally obtain catalyst H.

[0079] Examples 7-12

[0080] The catalysts of Examples 1-6 were evaluated by fixed bed reaction, with hexadecene and benzene (benzene to olefin molar ratio = 10) as raw materials. The reaction temperature was 140° C., the reaction pressure was 2.2 MPa, and the WHSV and results are shown in Table 1.

[0081] Comparative Examples 3-4

[0082] The catalysts of Comparative Examples 1-2 were evaluated using the same reaction evaluation conditions and raw materials as in Examples 7-12. The results are shown in Table 1.

[0083] As can be seen from the table, the catalysts prepared by the present invention all show excellent catalytic performance. Different types of MWW molecular sieves have a slight effect on the catalyst performance, but can maintain excellent catalytic performance. Mesoporous modified molecular sieves with different modification treatment methods can all play a good role in the catalyst. Different types of oxide binders have little effect on the catalyst performance, and can maintain excellent catalytic performance. These results show that the catalyst of the present invention not only has high activity and high selectivity, but also has excellent stability and is suitable for long-term continuous reaction.

[0084] In addition, alkylation reactions were carried out using normal olefins of different carbon chain lengths and a mixture of normal isomerized olefins as raw materials. The results showed that the catalysts of the present invention all exhibited excellent catalytic performance, further verifying the applicability of the catalysts and having broad application prospects.

[0085] Table 1

[0086] Feedstock Catalyst <![CDATA[WHSV(h -1 )]]> Conversion(%) LAB Selectivity (%) TOS(h) Example 7 1-Hexadecene A 4.4 92.6 81.3 261 Example 8 1-Tetradecene D 3.9 85.9 84.7 125 Example 9 1-Dodecene E 3.4 94.1 74.8 124 Example 10 n-Dodecene and iso-dodecene F 3.7 90.5 85.7 125 Embodiment 11 1-Hexadecene G 4.0 90.8 72.3 100 Example 12 <![CDATA[C 12-16 Normal Olefins]]> H 3.8 88.0 70.2 111 Comparative Example 3 1-Hexadecene B 4.3 86.6 31.4 125 Comparative Example 4 1-Dodecene C 4.0 63.5 38.4 99

[0087] Embodiment 13

[0088] Using the catalyst A prepared in Example 1, the effects of different reaction conditions on the synthesis of long-chain alkylbenzenes were investigated.

[0089] Fixed reaction pressure 2.2MPa, WHSV=4h -1 , the molar ratio of benzene to 1-tetradecene was 10:1, the reaction temperature was changed, and the reaction evaluation was carried out in a fixed bed for 24 hours. The reaction results are shown in Table 2 below.

[0090] Table 2

[0091] Reaction temperature (℃) 1-Tetradecene conversion rate (%) Monoalkylbenzene selectivity (%) 120 97.8 94.5 140 99.5 93.8 160 99.8 92.7

[0092] Fixed reaction temperature 140℃, WHSV=4h -1 , the molar ratio of benzene to 1-tetradecene was 10:1, the reaction pressure was changed, and the reaction evaluation was carried out in a fixed bed for 24 hours. The reaction results are shown in Table 3 below.

[0093] Table 3

[0094] Reaction pressure (MPa) 1-Tetradecene conversion rate (%) Monoalkylbenzene selectivity (%) 1.8 98.9 93.5 2.2 99.5 93.8 2.6 99.7 93.6

[0095] The reaction was evaluated in a fixed bed for 24 hours at a fixed temperature of 140°C, a pressure of 2.2 MPa, a molar ratio of benzene to n-tetradecene of 10:1, and a change in WHSV. The reaction results are shown in Table 4 below.

[0096] Table 4

[0097] <![CDATA[WHSV(h -1 )]]> 1-Tetradecene conversion rate (%) Monoalkylbenzene selectivity (%) 2 99.8 93.5 4 99.5 93.8 6 98.7 94.1

[0098] Fixed temperature 140℃, pressure 2.2MPa, WHSV4h -1 , changing the molar ratio of benzene to 1-tetradecene, and conducting the reaction evaluation in a fixed bed for 24 hours. The reaction results are shown in Table 5 below.

[0099] Table 5

[0100] Benzene to 1-tetradecene molar ratio 1-Tetradecene conversion rate (%) Monoalkylbenzene selectivity (%) 8:1 98.9 92.8 10:1 99.5 93.8 15:1 99.7 94.2

[0101] Examples 14-15

[0102] The catalyst prepared in Example 9 was washed and regenerated in a fixed bed at 250° C. and 3.2 MPa using benzene as a flushing agent to obtain a regenerated catalyst E.

[0103] The catalyst after the completion of Example 12 was calcined and regenerated. First, in an atmosphere with an oxygen ratio of 0% and the rest being nitrogen, the temperature was raised from 30°C to 190°C at 2°C / min, and the temperature was maintained for calcination for 3 hours. Then, the oxygen ratio was adjusted to 10%, and the rest was nitrogen. The temperature was continued to be raised to 350°C at 2°C / min, and the temperature was maintained for calcination for 4 hours. After completion, the oxygen ratio was adjusted to 20%, and the rest was nitrogen. The temperature was continued to be raised to 510°C at 2°C / min, and the temperature was maintained for calcination for 6 hours. Finally, the regenerated catalyst H was obtained.

[0104] The regenerated catalysts E and H were evaluated for reaction using a fixed bed, using the same reaction evaluation conditions and raw materials as in Examples 9 and 12. The reaction results are shown in Table 6 below.

[0105] Table 6

[0106] Feedstock Catalyst Conversion(%) LAB Selectivity (%) TOS(h) Embodiment 14 1-Dodecene Regeneration E 92.5 78.5 72 Embodiment 15 <![CDATA[C 12-16 Normal Olefins]]> Regeneration H 86.8 65.4 64

[0107] The results showed that the regenerated catalyst maintained high activity and selectivity when reacted under the same conditions as in the previous example.

Claims

1. A solid acid catalyst for synthesizing long-chain alkylbenzene, characterized in that: The composition includes the following components by mass: 10-55% MWW molecular sieve; 35-75% modified molecular sieve containing mesopores; and 5-20% oxide binder.

2. The solid acid catalyst according to claim 1, characterized in that The weight percentage of the MWW molecular sieve is 20-40%, the weight percentage of the modified molecular sieve containing mesopores is 50-70%, and the weight percentage of the oxide binder is 8-15%.

3. The solid acid catalyst according to claim 1 or 2, characterized in that The MWW molecular sieve has a staggered stacking structure and a mesopore volume of more than 0.5 cm 3 / g; The modified molecular sieve containing mesopores is a FAU or BEA type molecular sieve having a mesoporous structure of 3-50 nm; And / or, the oxide binder is one or more of alumina, pseudo-boehmite, silicon oxide, kaolin and zirconium oxide.

4. The method for preparing a solid acid catalyst as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The MWW type molecular sieve and the modified molecular sieve containing mesopores are prepared respectively; Mix the two molecular sieves according to a predetermined ratio; Add oxide binder and mix well; The solid acid catalyst is obtained by molding, drying and calcining.

5. The preparation method according to claim 4, characterized in that: The preparation process of the MWW molecular sieve is as follows: a proper amount of silicon source, aluminum source, template agent and deionized water are fully mixed and aged, and auxiliary agents are selectively added at the same time, and the mother liquor is continuously charged into a pressure container, and then crystallized in a homogeneous reactor at a certain temperature, and then the product is separated, washed, dried and calcined to finally obtain the MWW molecular sieve; and / or, The modified molecular sieve containing mesopores is prepared by one or more of the following methods: acid treatment, alkali treatment and steam treatment.

6. The preparation method according to claim 5, characterized in that: The silicon source is selected from one or more of tetraethyl orthosilicate, silica sol, precipitated silica, and fumed silica; and / or, The aluminum source is selected from one or more of aluminum nitrate, aluminum chloride and aluminum sec-butoxide; and / or, The template agent is selected from one of diethyldimethylammonium hydroxide, hexamethyleneimine and pentamethylammonium bromide; and / or, The MWW molecular sieve is prepared by a hydrothermal synthesis method at 120-200° C. and the crystallization time is 72-400 hours.

7. The preparation method according to claim 5, characterized in that: The alkali solution used in the alkali treatment is a sodium hydroxide solution, a mixed solution of tetrapropylammonium hydroxide and sodium hydroxide, or a recovered liquid after crystallization and solid separation during the preparation of the MWW molecular sieve; And / or, the acid concentration used in the acid treatment and the alkali concentration used in the alkali treatment are both 0.1-2 mol / L, the treatment temperature is 40-100° C., and the treatment time is 0.25-24 hours; And / or, the calcination temperature is 450-650° C., the time is 2-48 hours, and the calcination process is carried out in an air atmosphere or an inert gas atmosphere.

8. Use of a solid acid catalyst in the synthesis of long-chain alkyl aromatics, characterized in that: The solid acid catalyst is prepared by the preparation method described in any one of claims 1 to 3 or any one of claims 4 to 7, and the long-chain alkyl aromatic hydrocarbons include long-chain alkylbenzenes, long-chain alkyltoluenes and long-chain alkylnaphthalenes.

9. The use according to claim 8, characterized in that: The synthesis reaction conditions of the long-chain alkyl aromatics are: temperature 100-220°C, pressure 0.1-4.0MPa, mass space velocity 0.1-10h -1 , the molar ratio of aromatics to olefins in the raw material (5-30): 1; The olefin is C 10 -C 20 normal olefins within the range, or C 10 -C 20 A mixture of normal olefins and isoolefins within the range of C 10 -C 20 The range contains a mixture of normal and isomeric alkanes, olefins and aromatics.

10. The use according to claim 8, characterized in that: The regeneration method of the solid acid catalyst is as follows: Use benzene or a mixture of benzene and other light hydrocarbons in a certain proportion as a flushing agent to wash and regenerate the catalyst at a certain temperature and pressure; or, The catalyst is calcined and regenerated in an atmosphere containing a certain proportion of oxygen.

11. The use according to claim 10, characterized in that: The temperature range of the washing regeneration is selected from 150-280° C., the pressure range is selected from 1.5-4.0 MPa, and the duration is selected from 1-48 hours; and / or, The oxygen ratio of the calcination regeneration is 0-30%, and the rest is inert gas. The calcination process is to heat from a lower initial temperature to a certain temperature platform at a certain heating rate, and calcine at this temperature for a certain time, and then continue to heat to a higher temperature platform for calcination for a certain time, and complete regeneration after calcination at 1 to 4 temperature platforms, wherein the heating rate is 0.5-3.0°C / min, the calcination temperature is selected from the range of 150-650°C, and the calcination time is selected from 1-20 hours.

12. The use according to claim 8, characterized in that: The molecular sieve specific surface area of ​​the solid acid catalyst is 300-850m 2 / g, with a total pore volume of 0.3-1.3cm 3 / g, of which the mesopore volume accounts for 50-80% of the total pore volume.

13. Application of solid acid catalyst in high value utilization of Fischer-Tropsch synthesis products, characterized in that: The solid acid catalyst is prepared by any one of claims 1 to 3 or any one of claims 4 to 7, The solid acid catalyst is used for the alkylation reaction of α-olefins obtained by Fischer-Tropsch synthesis with aromatic hydrocarbons to prepare long-chain alkyl aromatic hydrocarbons.

Citation Information

Patent Citations

  • Method of preparing linear alkylbenzene

    CN101058523A

  • Production method for linear alkyl benzene

    CN108569945A

  • A method for producing highly selective linear alkylbenzenes

    CN113620766B

  • Solid acid catalyst for synthesizing long-chain alkylbenzene and preparation method of solid acid catalyst

    CN115646539A

  • Alkylbenzene preparation method

    CN116354782A